Penalaran Proporsional Siswa SMP dalam Menyelesaikan Masalah Missing Value dan Comparison Berdasarkan Gaya Kognitif Sistematis - Isman M. Nur; Diah Prawitha Sari (Peneliti.net, 2022)
This study aims to describe students' proportional reasoning based on systematic cognitive style in solving missing value and comparison problems. This research is a qualitative research with an exploratory descriptive approach. The research subjects were seventh grade students of SMP Negeri 4 Ternate City. Research subjects were not chosen randomly, but were chosen based on consideration of communication skills both oral and written in solving problems. The research instrument consisted of two questions as well as an assistive instrument in the form of an interview guide which was adapted to the conditions at the time of research in the field. The results of this study are, 1) students make plans in advance to write down two quantities that have variations together and also see the suitability between the two different variations, 2) students can understand the proper procedure for presenting quantities in the form of ratios, 3) students can solve problems according to detailed steps based on multiplicative concepts by using multiplication strategies involving proportion situations, 4) students give reasons based on data or information related to problems and can be solved with proportional ideas